(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Introduzione - 2. L’odierno dibattito sulle prerogative patriarcali costantinopolitane e il gathering di Amman - 3. La ratio attributiva delle prerogative ecclesiastiche romane al vescovo di Costantinopoli-ΝέαςῬώμης - 4. Le prerogative ecclesiastiche costantinopolitane - 5. Il conferimento imperiale del titolo patriarcale al vescovo di Roma e di patriarca ecumenico al vescovo di Costantinopoli-Νέας Ῥώμης - 6. L’ecumenicità dell’omofonia patriarcale - 7. Osservazioni finali. Patriarchal ecumenical homophony ABSTRACT: The establishment in 2019 of a new Ukrainian autocephaly raises the question of the legal basis of exclusive Constantinopolitan canonical prerogatives. As is known, after the Edict of Thessalonica of 380, can. cost. 3 of 381 attributes the Roman prerogatives to the bishop of Constantinople-Νεα Ρωμη.The ethnarchical religious role, assumed by the Roman bishop, guardian of the Romanitas, (conceived as the apostolic heritage of the Roman church), determines the Eastern emperors to confer the patriarchal title (previously reserved for the Jewish etnarch of Palestine), to Roman pope and ecumenical patriarch, to the bishop of Constantinople, which became the only seat of the imperium.The Justinian articulation of the ecclesiastical order comes to highlight in the homophony of patriarchs the attestation of the unity, doctrinal and disciplinary, in the Church of the ecumenical empire. Therefore, today’s panorthodox reception of Ukrainian autocephaly cannot be considered an ecclesial burden due to the universal canonical authority of the patriarchate of Constantinople. Consequently, the primates cannot accept it in the name of the respective autocephalous Church, in contrast with canon 34. In respect of the nomocanonical tradition, today’s Ukrainian controversy must therefore be submitted to the assembly of patriarchs in order to reach a canonical unanimous (homophone) solution to the controversy.